Comparison of erythrocyte distribution width, mean platelet volume and platelet distribution width in patients with obstructive sleep apnea syndrome - Çelikhisar, Hakan; Daşdemir İlkhan, Gülay (Journal of Surgery and Medicine, 2019)
Aim: Reliable markers are needed to evaluate the response of chronic inflammation in obstructive sleep apnea syndrome (OSAS) to positive airway pressure (PAP) treatment. In this study, we aimed to investigate the long-term effects of PAP treatment on hemogram parameters and its relationship with inflammation and severity of disease in OSAS patients. Methods: Based on polysomnography (PSG) results, 61 (35.1%) participants and 113 OSAS patients (64.9%) were included in the control and study groups, respectively. Among these patients, 31.6% had moderate and 33.3% had severe OSAS. MPV, PDW, RDW, hemoglobin, hemotocrit, platelet values were evaluated and compared between the groups at six and twelve-month intervals in this prospective cohort study. Results: All participants (n=174) were males aged between 33-62 years. Hemoglobin, hematocrit and MPV values of the study group were significantly higher at the baseline (P=0.008, P=0.007, P=0.004, respectively) and had decreased significantly by the 6th and 12th months in both groups P=0.004, P=0.003, P=0.004, respectively). Conclusion: All participants were chosen from males to exclude hormonal effects on hemogram parameters, which also turned out to be a limitation of this study. Our study showed a correlation between MPV, RDW, PDW, hemoglobin and hematocrit values and OSAS severity. MPV, RDW, hemoglobin, hematocrit and platelet may be considered inexpensive biomarkers easily obtained from blood tests which make it useful in determining the severity of OSAS and prioritizing patients for PAP therapy.